2019
DOI: 10.5539/jpl.v12n1p108
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Dynamics and Operations of Civil Society in the 21st Century: A Literature Review

Abstract: This article sets out to review the extant literature on civil society. Indeed the literature on civil society abounds with several views and perspectives, especially on the theoretical debates on the concept. However, in order to avoid the unnecessary entanglement of the unending theoretical debates that have characterized the subject, the article focuses on the activities and operations as well as the usefulness of civil society in the twenty first century. The article consequently tries to identify the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Civic engagement movements have perhaps never been more intense than in the 21st century. The start of the 21st century was greeted with several civic movements that influenced the global political, social, and economic developments (Botchway, 2019;Simiti, 2017). The 21st century is characterised as a period of rapid change worldwide that places knowledge as an important commodity which has become democratised thanks to Internet technology (Ausman, 2010;Lemke & Coughlin, 2009).…”
Section: Social Mediamentioning
confidence: 99%
“…Civic engagement movements have perhaps never been more intense than in the 21st century. The start of the 21st century was greeted with several civic movements that influenced the global political, social, and economic developments (Botchway, 2019;Simiti, 2017). The 21st century is characterised as a period of rapid change worldwide that places knowledge as an important commodity which has become democratised thanks to Internet technology (Ausman, 2010;Lemke & Coughlin, 2009).…”
Section: Social Mediamentioning
confidence: 99%
“…This stems from the fact that studies have over the years indicated that across the globe, CSOs are usually a key component in educating the populace and enhancing the capabilities as well as participations in the overall development agenda. (Botchway, 2019a; Thus their effective engagement by the State in the implementation process would have a lot of positive implications for the entire process in the long run. Civil society organisations are important entities that ensure capacity building of various stakeholders and institutions.…”
Section: Effective Engagement and Involvement With Civil Societymentioning
confidence: 99%